Detecting Terrestrial Nutrient Limitation: A Global Meta-Analysis of Foliar Nutrient Concentrations after Fertilization - Ostertag, Rebecca; DiManno, Nicole M. (Frontiers in Earth Science, 2016)
Examining foliar nutrient concentrations after fertilization provides an alternative method for detecting nutrient limitation of ecosystems, which is logistically simpler to measure than biomass change. We present a meta-analysis of response ratios of foliar nitrogen and phosphorus (RRN, RRP) after addition of fertilizer of nitrogen (N), phosphorus (P), or the two elements in combination, in relation to climate, ecosystem type, life form, family, and methodological factors. Results support other meta-analyses using biomass, and demonstrate there is strong evidence for nutrient limitation in natural communities. However, because N fertilization experiments greatly outnumber P fertilization trials, it is difficult to discern the absolute importance of N vs. P vs. co-limitation across ecosystems. Despite these caveats, it is striking that results did not follow “conventional wisdom” that temperate ecosystems are N-limited and tropical ones are P-limited. In addition, the use of ratios of N-to-P rather than response ratios also are a useful index of nutrient limitation, but due to large overlap in values, there are unlikely to be universal cutoff values for delimiting N vs. P limitation. Differences in RRN and RRP were most significant across ecosystem types, plant families, life forms, and between competitive environments, but not across climatic variables.